2020
DOI: 10.1001/jama.2020.14348
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Statewide School Closure and COVID-19 Incidence and Mortality in the US

Abstract: In the US, states enacted nonpharmaceutical interventions, including school closure, to reduce the spread of coronavirus disease 2019 (COVID-19). All 50 states closed schools in March 2020 despite uncertainty if school closure would be effective. OBJECTIVE To determine if school closure and its timing were associated with decreased COVID-19 incidence and mortality. DESIGN, SETTING, AND PARTICIPANTS US population-based observational study conducted between March 9, 2020, and May 7, 2020, using interrupted time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
455
1
14

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 449 publications
(525 citation statements)
references
References 20 publications
(28 reference statements)
38
455
1
14
Order By: Relevance
“…The overall doubling time (first 21 days of the epidemic) in each state was also correlated with demographic parameters. However, in line with past work [28,40,41], we show early https://doi.org/10.1371/journal.pone.0240648.g002…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…The overall doubling time (first 21 days of the epidemic) in each state was also correlated with demographic parameters. However, in line with past work [28,40,41], we show early https://doi.org/10.1371/journal.pone.0240648.g002…”
Section: Plos Onesupporting
confidence: 91%
“…We did not examine the doubling time after 21 days as some states were already recorded a decrease in the daily number of cases per day at that point (S2 Fig). The early doubling time should not be strongly correlated with government interventions as these were often implemented late and there is a delay in which effects from government actions are detectable [28].…”
Section: Methodsmentioning
confidence: 99%
“…Tull et al (2020) suggested that measures such as home con nement, social distancing, and quarantine to control infection greatly contribute to a sense of loneliness among young people as they restrict them from socialising with their peers. In addition, closure of schools could partly play a role in the development of loneliness among students as school routines and activities were identi ed as essential coping mechanisms, especially for young people (Auger et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These associations were largest in states with low case numbers at the time of school closure. 30 In a prospective cohort study of 144 countries, states or provinces between March 7 and March 27, 2020, Jüni et al found a 37% reduction in epidemic growth associated with school closures (95% confidence interval 22 to 48%). 31 The other public health interventions studied were restrictions of mass gatherings and social distancing measures.…”
Section: Ecological Studies On School Closuresmentioning
confidence: 99%
“…31 In a subsequent retrospective study in 149 countries or regions between January 1 and May 30, 2020, Islam et al found school closures, in combination with other types of public health interventions, to be associated with an average reduction in incidence of 13% (95% confidence interval 11 to 15%). 32 All three studies on school closures [30][31][32] were observational, ecological studies. Causality can therefore not be established.…”
Section: Ecological Studies On School Closuresmentioning
confidence: 99%